Regularization in quantum field theories - Fabiano, Nicola (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: The principal techniques of regularization schemes and their validity for gauge field theories are discussed. Methods: Schemes of dimensional regularization, Pauli–Villars and lattice regularization are discussed. Results: The Coleman–Mandula theorem shows which gauge theories are renormalizable. Conclusion: Some gauge field theories are renormalizable, the Standard Model in particular.